Financing, reputation and information disclosure quality in the Chinese market. Issue 9 (19th February 2016) - Mi, Jianhua; Sheng, Hong; Elrod, Cassandra
ABSTRACT: In this article, we propose a theoretical model based on the reputation theory and hypothesize a positive relation between the information disclosure quality and the company's refinancing decision. We collected data from the listed companies, which refinances in Shenzhen main board and SME board during 2006–2012, as a panel sample, and tested the hypothesis empirically. The results indicate that there exists a significant positive correction short-term relation between refinancing decision and the information disclosure quality, but in the long term the relationship between the information disclosure quality and refinancing decision is not significant.